Take One, Two, Three... aus der Sammlung Speck Köln - Heynen, Julian; Krystof, Doris; Speck, Reiner; Zweite, Armin (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
Beuys, Joseph ; Broodthaers, Marcel ; Buren, Daniel ; Byars, James Lee ; Förg, Gunther ; Herold, Georg ; Kawara, On ; Kippenberger, Martin ; Kounellis, Jannis ; Pettibon, Raymond ; Polke, Sigmar ; Trockel, Rosemarie ; Weiner, Lawrence
Verzeichnis der monografischen Publikationen zur Sammlung Speck p. 87
biog., ind. tent., bibliog. p.82-86
Duits
Take One, Two, Three... aus der Sammlung Speck Köln, K21 Kunstsammlung Nordrhein-Westfalen Düsseldorf, 21. April 2002 - 27. April 2003
boek